New theropod (Tetanurae: Avetheropoda) material from the 'mid'-Cretaceous Griman Greek Formation at Lightning Ridge, New South Wales, Australia. Issue 1 (30th January 2019) - Brougham, Tom; Smith, Elizabeth T.; Bell, Phil R.
Abstract : The limited fossil record of Australian Cretaceous theropods is dominated by megaraptorids, reported from associated and isolated material from the Early Cretaceous of Victoria and the 'Mid'-Cretaceous of central-north New South Wales and central Queensland. Here, we report on new postcranial theropod material from the early Late Cretaceous Griman Creek Formation at Lightning Ridge. Among this new material is an associated set consisting of two anterior caudal vertebrae and a pubic peduncle of the ilium, to which a morphologically similar partial vertebral centra from a separate locality is tentatively referred. These elements display a combination of characteristics that are present in megaraptorid and carcharodontosaurid theropods, including camellate internal organization of the vertebral centra, ventrally keeled anterior caudal centra and a pubic peduncle of the ilium with a ventral surface approximately twice as long anteroposteriorly as mediolaterally wide. Unfortunately, a lack of unambiguous synapomorphies precludes accurate taxonomic placement; however, avetheropodan affinities are inferred. This new material represents the second instance of a medium-sized theropod from this interval, and only the third known example of associated preservation in an Australian theropod. Additional isolated theropod material is also described, including an avetheropodan femoral head that shows similarities to Allosaurus and Australovenator, and a mid-caudal vertebral centrum bearing pneumatic foraminae and extensive camellae that is referrable to Megaraptora and represents the first axial skeletal element of a megaraptorid described from Lightning Ridge.